Multifunctional hybrid micelles with tunable active targeting and acid/phosphatase-stimulated drug release for enhanced tumor suppression. (March 2018) - Liu, Xuhan; Li, Yinghuan; Tan, Xi; Rao, Rong; Ren, Yuanyuan; Liu, Lingyan; Yang, Xiangliang; Liu, Wei
Abstract: Therapeutic efficacy of conventional single PEGylated polymeric micelles is significantly reduced by limited endocytosis and intracellular drug release. To improve drug delivery efficiency, poly (ethylene glycol)-block-poly (l -lactic acid)/(Arg-Gly-Asp-Phe)-poly (aminoethyl ethylene phosphate)-block-poly (l -lactic acid) (PEG-PLLA/RGDF-PAEEP-PLLA) hybrid micelles with tunable active targeting and acid/phosphatase-stimulated drug release are developed. The optimized hybrid micelles with 6 wt % of RGDF have favorable in vitro and in vivo activities. The hybrid micelles could temporarily shield the targeting efficacy of RGDF at pH 7.4 due to the steric effect exerted by concealment of RGDF peptides in the PEG corona, which strongly decreases the clearance by mononuclear phagocyte system and consequently improves the tumor accumulation. Inside the solid tumor with a lower acidic pH, the hybrid micelles restore the active tumor targeting property with exposed RGDF on the surface of the micelles because of the increased protonation and stretching degree of PAEEP blocks. RGDF-mediated endocytosis improves the tumor cell uptake. The hybrid micelles would also enhance intracellular drug release because of the hydrolysis of the acid/phosphatase-sensitivity of PAEEP blocks in endo/lysosome. Systemic administration of the hybrid micelles significantly inhibits tumor growth by 96% due to the integration of enhanced circulation time, tumor accumulation, cell uptake and intracellular drug release.